Long-distance transport of hair lambs: effect of location in pot-belly trailers on thermo-physiology, welfare and meat quality - Miranda-de la Lama, G. C.; Rodríguez-Palomares, M.; Cruz-Monterrosa, R. G.; Rayas-Amor, A. A.; Pinheiro, R. S.B. [UNESP]; Galindo, F. M.; Villarroel, M. (Springer Nature, 2018)
Livestock transport exposes animals to a range of potential stressors that may compromise their welfare and final product quality, and those effects typically increase with the distance travelled. In North America, producers often use pot-belly vehicles for long hauls but little is known about their suitability for transporting lambs. We followed two long-distance trips using pot-belly trailers carrying 500 lambs (each) from Northern to Central Mexico in winter, to measure possible effects on animal welfare and meat quality. Sixty lambs per trip were placed at different locations within the pot-belly trailer. Animals were equipped with iButton Thermochron® temperature devices, which registered body temperature throughout pre- and post-slaughter stages. Despite the rather cool winter conditions, lambs placed in the “belly” and “nose” compartments had higher body temperatures at loading, during transport and lairage and after slaughter (carcass temperature). Those lambs also had higher levels of plasma cortisol, glucose and creatine kinase (CK), and a higher neutrophil/lymphocyte ratio. Regarding meat quality, ultimate pH (24 h) was higher in all locations, especially in LT4 location. Overall, the results suggest a link between thermal stress during transport, elevated physiological indicators of stress and poorer meat quality.
Keywords: Hair lambs; iButton Thermochron®; Long-distance transport; Mexico; Stress hyperthermia